Linkages between modern benthic foraminiferal assemblages and environmental conditions at continental slope depths: From Baffin Bay to the Labrador Sea - Joanna Davies; Anne Jennings; Alice Carter-Champion; William J. D'Andrea; Cara Fritz; Erin E. Gregory; David J. Harning; Robert Kelleher; Alan C. Mix; Katherine Stelling; Joseph S. Stoner; Maureen H. Walczak; et al. (Marine Micropaleontology, 2025)

Influences of extratropical water masses on equatorial Pacific cold tongue variability during the past 160 ka as revealed by faunal evidence of planktic foraminifers - Pai‐Sen Yu; Markus Kienast; Min‐Te Chen; Isabel Cacho; Jos Abel Flores; Mahyar Mohtadi; Alan C. Mix (Journal of Quaternary Science, 2012)
Glacial cooling (∼1–5°C) in the eastern equatorial Pacific (EEP) cold tongue is often attributed to increased equatorial upwelling, stronger advection from the Peru–Chile Current (PCC), and to the more remote subpolar southeastern Pacific water mass. However, evidence is scarce for identifying unambiguously which process plays a more important role in driving the large glacial cooling in the EEP. To address this question, here we adopt a faunal calibration approach using planktic foraminifers with a new compilation of coretop data from the eastern Pacific, and present new downcore variation data of fauna assemblage and estimated sea surface temperatures (SSTs) for the past 160 ka (Marine Isotope Stage (MIS) 6) from ODP Site 1240 in the EEP. With significant improvement achieved by adding more coretop data from the eastern boundary current, our downcore calibration results indicate that most of the glacial cooling episodes over the past 160 ka in the EEP are attributable to increased influence from the subpolar water mass from high latitudes of the southern Pacific. By applying this new calibration of the fauna SST transfer function to a latitudinal transect of eastern Pacific (EP) cores, we find that the subpolar water mass has been a major dynamic contributor to EEP cold tongue cooling since MIS 6. Copyright © 2012 John Wiley & Sons, Ltd.

Bias and uncertainty of δ13CO2 isotopic mixing models - Zachary E. Kayler; Lisa Ganio; Mark Hauck; Thomas G. Pypker; Elizabeth W. Sulzman; Alan C. Mix; Barbara J. Bond (Oecologia, 2010)